Integritas Auditor dan Etika Profesional: Faktor Penentu Kualitas Audit yang Efektif : Survey pada Auditor di BPKP Perwakilan Sulawesi Selatan - Sufiati; Muhammad, Irsyad (Insan Cita Bongaya Research Journal, 2025)
The purpose of the study was to test and analyze the influence of auditor integrity and professional ethics on audit quality at the South Sulawesi Provincial Representative BPKP. The respondents or research sample were auditors totaling 63 people. Data collection uses questionnaire techniques. Data analysis using multiple regression with SPSS application. The results of the study show that integrity has a significant positive effect on audit quality. Professional ethics have a significant positive effect on audit quality.